Tips on Operating a Profitable Greenhouse Business - Cloyd, Raymond A.; Faust, James E.; Konjoian, Peter; Uva, Wen-fei L.; Williams, Kimberly A. (O.F.A. Services, Inc., 2011)
Chapters include Six Levels of Greenhouse Cost Accounting; Using Spreadsheets as Cost Analysis Tools; Overhead or Fixed Costs; Square Foot Weeks: Applying Overhead Costs to the Greenhouse Production Area; Variable Costs: General Discussion; Calculating Variable Costs; Labor Costs; Calculating Costs of Propagation; Calculating Costs of Pest Management; Greenhouse Productivity; Comparing Crop Revenue; Square Foot Revenue Tables; Pricing and Square Foot Revenue Examples; Completing the Profitability Equation; Profitability in the Greenhouse Industry.
Keywords: Greenhouse management